Penilaian Kinerja Operasi dan Pemeliharaan Menuju Bendungan Serbaguna Wonogiri yang Berkelanjutan - Setiawan, Rizki Bangun; Suharyanto, Suharyanto; Sukamta, Sukamta (Universitas Batanghari Jambi, 2026)
Gajahmungkur also known as the Wonogiri multipurpose dam, is a long-standing dam in Wonogiri Regency, Central Java Province. After nearly five decades of operation, an evaluation of the dam's operational and maintenance performance is necessary to ensure its continued function. This study aims to analyze the actual condition of the Wonogiri multipurpose dam through a condition index assessment method for each dam component based on primary and secondary data. The assessment process is carried out by determining a condition index value that reflects the level of performance and safety of the dam area. The analysis results show that the Wonogiri multipurpose dam obtained a condition index value of 3, which is included in the moderate damage category. This finding indicates the need for maintenance measures to prevent further damage. Based on the results of observations, dense grass growth, sedimentation, and the need for repairs to the hydromechanical equipment were found. This emphasizes the importance of proper evaluation and repair for optimal and sustainable dam operation. The recommendations from this study are expected to guide more effective and efficient dam management in the future.